Liquid Chromatography‒Tandem Mass Spectrometry Analysis of Primary Metabolites and Phenolic Acids Across Five Citrus Species - Yujiao Peng; Xueyu Cui; Manman Sun; Xiaojuan Huang; Ke Tang; Baoqing Hu; Hongze Liao (Current Issues in Molecular Biology)
Citrus is a globally consumed fruit with great popularity, yet systematic analyses of primary metabolites across major varieties remain scarce, with phenolic acids as an auxiliary focus due to their flavor relevance. In this study, the primary metabolites and phenolic acids of five citrus varieties were analyzed via liquid chromatography‒tandem mass spectrometry (LC–MS/MS). The analysis revealed that five different citrus varieties contained 342 primary metabolites and 77 phenolic acids. The PCA clearly distinguished the metabolites of various citrus varieties. Compared with the pomelo group, the lemon group presented the most differentially abundant metabolites, whereas the kumquat and navel orange groups presented the fewest. An examination of metabolic pathways with notable disparities revealed that phenylpropanoid biosynthesis and the biosynthesis of amino acids significantly varied between varieties. This study elucidates primary metabolic networks underlying citrus flavor diversification, with phenolic acids providing secondary modulation insights. Moreover, this study provides a theoretical foundation for enhancing the flavor of citrus fruits.